The Effect of Mental Accounting and Heuristics on Financial Behavior with Self-Efficacy as Moderator - Barek, Titya Advianti P.; Djuuna, Meykel; Danang, Surya (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the effect of mental accounting and heuristics on financial behavior, with self-efficacy as a moderating variable in Insan Corporation Manado employees. This research is motivated by the empirical phenomenon that the majority of employees show financial behavior that does not reflect the principles of good financial management, such as the tendency to make impulsive purchases, lack of budget planning and the dominance of emotional decisions. The method used is a quantitative approach with survey techniques using online questionnaires (google form) distributed to 131 respondents. Data analysis was carried out using Structural Equation Modeling - Partial Leas Squares (SEM-PLS). The results showed that mental accounting has a positive and significant influence on financial behavior with a sig. value of 0.000, as well as heuristics have a positive and significant influence on financial behavior with a sig. value of 0.000. Furthermore, self-efficacy is proven to positively and significantly moderate the relationship between mental accounting and financial behavior (sig. value of 0.045), and negatively moderate the relationship between heuristics and financial behavior (sig. value of 0.043). Thus, it can be concluded that mental accounting and heuristics play a significant role in shaping employees' financial behavior, while self-efficacy is the main psychological factor that can strengthen or weaken their influence. A person's level of confidence in managing their finances plays an important role in encouraging more adaptive and rational financial behavior.